Ruby red / 1. - Gier, Kerstin, 1966- (Ruby Red Trilogy, 2012)
Sixteen-year-old Gwyneth Shepherd unexpectedly travels through time to the eighteenth century, and she must find out why her mother lied about her date of birth to hide her ability, research her history, and work with Gideon, another time traveler.